Evaluation of Malnutrition Risk in Lung Transplant Candidates Using the Nutritional Risk Index - Chohan, Karan (Transplant Direct, 2020)
BACKGROUND. Malnutrition in lung transplant (LTx) candidates is an important risk factor for adverse outcomes. We sought to evaluate the Nutritional Risk Index (NRI) in LTx candidates, a validated measure of malnutrition risk in chronic disease. We aimed to characterize malnutrition risk using NRI, evaluate change in body weight between nutritional risk groups, and assess association of malnutrition risk with pretransplant and posttransplant outcomes. METHODS. Retrospective, single-center cohort study of LTx candidates (2014–2015) evaluated by a dietitian before listing. Nutritional parameters, weight change pretransplant and posttransplant, and clinical outcomes were abstracted up to 1-year posttransplant. NRI was calculated as follows: (1.519 × albumin) + (41.7 × current weight/ideal weight) with high malnutrition risk defined as the lowest quartile of NRI for cystic fibrosis (CF) and non-CF patients. RESULTS. The cohort comprises 247 LTx candidates (57% male; median age 59 y; non-CF 88%). Non-CF candidates had a greater mean NRI compared with CF patients (109 ± 11 versus 95 ± 12; P < 0.0001). 86% with high malnutrition risk maintained/gained weight (≥5%) pretransplant. In 196 LTx recipients, malnutrition risk was not associated with hospital stay, discharge disposition, or 1-year mortality. The median percent weight gain for LTx recipients in the first year was 10.5% (4.0–20.1), with high malnutrition risk recipients having comparable or greater weight gain to the low-risk group (mean difference for non CF: 6.8%; P = 0.02 and CF: −3.8%; P = 0.65). CONCLUSIONS. Malnutrition risk assessed with NRI was not prognostic of posttransplant outcomes in this retrospective cohort. LTx candidates with high malnutrition risk were able to maintain their weight pretransplant and demonstrated considerable weight gain in the first-year posttransplant.